PENGARUH PARTISIPASI ANGGARAN PADA SENJANGAN ANGGARAN DEGAN GAYA KEPEMIMPINAN DAN KARAKTER PERSONAL SEBAGAI VARIABEL PEMODERASI - Pradnyandari, Shinta Dewi; Krisnadewi, Komang Ayu (E-Jurnal Akuntansi, 2014)
The purpose of this paper is to determine whether the effect on the budgetary participation and budgetary slack to know the role of leadership style and personal character in relation to the budget participation budgetary slack. The respondents in the study, namely the head of the field / section, head section, and the head of the sub-section on education in the province of Bali as much as 40 on education. The selection of the sample using purposive sampling method, diuii using multiple linear regression analysis with MRA (Moderated Regression Analysis). Based on the results is unknown if the budgetary participation has a positive effect on budgetary slack and leadership style and personal character have negative effect on the relationship with the participation of budgetaryslack.
Keywords: Participation Budget, budgetary slack, Leadership Style, Personal Character